If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + -12 = -20 Reorder the terms: -12 + -4y = -20 Solving -12 + -4y = -20 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -4y = -20 + 12 Combine like terms: -12 + 12 = 0 0 + -4y = -20 + 12 -4y = -20 + 12 Combine like terms: -20 + 12 = -8 -4y = -8 Divide each side by '-4'. y = 2 Simplifying y = 2
| 3(b+6)=-28+4a | | 116-20h=996 | | 5-x=-4.5 | | 3x^2-57x+54=0 | | 6x-2+-15x=-10x | | 4x-1+7x+3=8x+4+-3x+10 | | 124=8u-44 | | -5y+8=-8y-4 | | -7(k+9)=9k-1 | | =0.02 | | -15+3y=33 | | t^3-21t+20=0 | | (x-9)4=y+9 | | r-31=6 | | 4*3b=12 | | x(0.5)+40=x(0.15) | | -8k+112=816 | | (-5x-14)(51)= | | x^2-15x+52=0 | | -15+9x=-42 | | 2m+5-8m=3m | | 96=10f+6 | | 3(x+5)-14=-2(x+3)+12 | | 3+5a=53 | | 5x--=x+15 | | 6-9=8x+11 | | 3x+2x+y=3y+2 | | x+1=5x-10 | | -12=g/4-2 | | 10x-92=6x-24 | | 20-2r=16 | | 2+7(3x+1)=4x-10 |